(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Diabetes mellitus remains a major global health challenge associated with complications such as neuropathy, nephropathy, and cardiovascular disorders. This study evaluated the antidiabetic potential of zinc oxide nanoparticles (ZnO-NPs) synthesised using the fruit extract of Balanites aegyptiaca through a green synthesis approach. The plant extract served as both a reducing and stabilising agent, and the formation of crystalline ZnO-NPs was confirmed by Fourier Transform Infrared (FTIR) and X-ray Diffraction (XRD) analyses. Diabetes was induced intraperitoneally in Wistar albino rats using streptozotocin (STZ, 55 mg/kg). STZ induction caused a significant increase in fasting blood glucose, total cholesterol, triglycerides, and LDL levels, along with a reduction in HDL, anaemia, and elevated liver enzymes (ALT, AST, ALP), indicating hepatic dysfunction and haematological disturbances. Oral administration of ZnO-NPs (2.5, 5, and 10 mg/kg) for 14 days significantly reversed these alterations in a dose-dependent manner. Treated rats exhibited reduced fasting blood glucose, normalised lipid profiles, restored haematological parameters, and improved liver enzyme levels. Histopathological examination of pancreatic tissues revealed marked Î²-cell regeneration and restored islet architecture, comparable to glibenclamide-treated rats. These findings suggest that B. aegyptiaca-mediated ZnO-NPs possess potent antidiabetic, hepatoprotective, and haematoprotective effects. The synergistic action between zinc and plant-derived phytochemicals enhances therapeutic efficacy, providing an eco-friendly and cost-effective nanotherapeutic for diabetes management.